Monitoring the Quality of Vannamei Shrimp (Litopenaeus vannamei) in Traditional Ponds in the Regencies of Lamongan and Gresik, as Suppliers for Fisheries Companies in East Java - Hermawan, Muhammad Ihffal Haikal; Rahim, Andi Rahmad; Aminin, Aminin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Vaname shrimp (Litopenaeus vannamei) is one of Indonesia's leading fisheries commodities. Lamongan and Gresik districts are one of the largest vaname shrimp producers in East Java. This research was conducted to determine differences in the growth of vanami shrimp, differences in the quality of vanami shrimp in terms of color, absolute weight, absolute length, and differences in methods of cultivating vanami shrimp in Rejosari Village, Lamongan Regency and Pandanan Village, Gresik Regency. This research was conducted in April-May 2024 using 4 ponds (2 in Lamongan and 2 in Gresik). The methods used are qualitative and quantitative methods, measuring the color of vanami shrimp using a color reader, testing weight and length using the t-test to determine significant values ​​between the 2 locations, differences in methods of cultivating vanami shrimp using interviews with farmers. The results of this study showed that the color quality of vaname shrimp, A (Rejosari Village, Lamongan) in the 1st replication (pond A1) and (pond A2) doc k2 30-doc to 65 showed quite good color values ​​except for pond A in the 1st replication (pond A1). The results of the absolute weight t-test are 0.30 > 0.05, while for the absolute long t-test it is 0.94 > 0.05. The results of interviews with farmers showed differences in the feed used, farmers A1 and A2 used traditional feed in the form of cassava which was grated and then dried, the artificial feed used for ponds A1 and A2 was (multi super feed). Meanwhile, in ponds B1 and B2, traditional feed was used in the form of steamed leftover rice and corn, the artificial feed used for ponds B1 and B2 was (karka).